Quantitative Characterization of Macrophage, Lymphocyte, and Neutrophil Subtypes Within the Foreign Body Granuloma of Human Mesh Explants by 5-Marker Multiplex Fluorescence Microscopy - Klinge, Uwe; Dievernich, Axel; Stegmaier, Johannes (Frontiers in Medicine, 2022)
Foreign bodies such as fibers of a surgical mesh induce a typical reaction with an inflammatory infiltrate that forms a surrounding granuloma. This infiltrate is dominated by macrophages, lymphocytes, and neutrophils, whereas its extent of collaboration is widely unknown. In the present study, we analyzed 12 samples of surgical meshes explanted from humans by multiplex analyses with three different 5-marker panels – 1. macrophage panel: CD68, CD86, CD105, CD163, and CD206; 2. lymphocyte panel: CD3, CD4, CD8, CD20, and CD68; and 3. neutrophil panel: CD15, Histone, MPO, NE, and CD68. Measurement of fluorescence intensity within nuclear masks resulting from DAPI nuclear staining allows exact quantification of cells considered “positive” at a user-defined mean intensity threshold of > 100. Obviously, however, there is no natural threshold as a biological criterion for intensity that separates “positive” stained cells from unstained cells (“negative”). Multiplex-staining of 5 markers always reveals a high rate of co-expression for almost all of the 25 possible marker combinations (= 32 combinations, when using 5 markers simultaneously). The present staining results demonstrate that various morphological and functional subtypes of macrophages, lymphocytes, and neutrophils are abundant in the foreign body granuloma, which were investigated by regions of interest with an area of 1 mm2. The widespread co-expression of two or more markers underscores the complex collaboration network of the inflammatory infiltrate. The ability to combine spatial distribution with exact numerical analysis may offer new perspectives for our understanding of the complex interactions in this multidimensional process.